ANALISIS PENGAKUAN PENDAPATAN BUNGA ATAS PEMBERIAN KREDIT MODAL KERJA PADA PT. BANK PERKREDITAN RAKYAT PRISMADANA - Korah, Timothy Ray; Saerang, David Paul Elia; Wokas, Heince (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
The largest bank revenue is interest income from credit. In general, bank lending business and one of the most interest product.Therefore the recognition and measurement of the right to credit interest income must be relevant, accurate, and accounted for, so the financial statements truly on the real financial position. The research aims to determine how the accounting treatment of the recognition of interest income on PT.BPR PRISMA DANA is already in appropriate with the applicable accounting standards, The method used in this research is descriptive analysis method. The results of research conducted in PT.BPR PRISMA DANA, showed recognition of loan interest income using the accrual basis or more leads to the realization of the concept.Except for interest income on loans classified as problematic (nonperforming) is recognized when it is received (cash basis). Interest income using the effective interest annuity system is calculated based on the remaining principal.